Targeting PIK3CB/YAP1 improves the sensitivity of paclitaxel by suppressing aging in head and neck squamous tumor cells - Junzhi Liu; Huimin Li; Ruotong Sun; Guoguang Ying; Zheng Liang (Cancer Cell International)
Abstract Background Tumor cell senescence reduces sensitivity to anticancer drugs, making senescent cell elimination an ideal strategy to enhance chemotherapy sensitivity. The interaction between the PI3K/Akt and Hippo/YAP1 pathways is increasingly studied, but the role of PIK3CB, YAP1, and their impact on senescence and chemotherapy sensitivity in head and neck tumors is unclear. Methods Public datasets (GEO, TCGA, HPA) were analyzed for PIK3CB expression and clinical associations. Immunohistochemistry, cell proliferation assays, DNA replication, colony formation, aging markers, and DNA damage assessments were conducted. Bulk and single-cell transcriptomics and proteomics data were analyzed. Cell passage effects on aging and the impact of PIK3CB modulation on YAP1 were evaluated. Potential drugs targeting PIK3CB were identified, and the effects of senescent cell clearance drugs on clonogenic abilities and chemotherapy sensitivity were assessed. Results Elevated PIK3CB expression in HNSCC tumors correlated with advanced stages, older age, and decreased survival. PIK3CB and YAP1 expressions were strongly correlated, impacting aging pathways and cellular proliferation. Modulation of PIK3CB affected tumor cell proliferation, aging, and DNA damage. The combined application of navitoclax and paclitaxel can reduce tumor cell proliferation and autonomous migration ability, influenced by the levels of PIK3CB. Conclusion High PIK3CB expression in head and neck cancers is linked to poor prognosis and advanced tumor grades. PIK3CB promotes cell proliferation and reduces aging via the YAP1 pathway. The combination of navitoclax and paclitaxel reduces tumor cell proliferation and autonomous migration ability, providing a basis for further exploration of increasing chemotherapy sensitivity.